The Relationship Between Corporate Social Responsibility and Corporate Financial performance: Factors that Moderate and Mediate the CSR-CFP Relationship - Deng, Yuqin (International Journal of Global Economics and Management, 2024)
Previous studies on the relationship between corporate social responsibility (CSR)and corporate financial performance (CFP)have not been conclusive. This paper reviews the literature on the relationship between corporate social responsibility (CSR) and corporate financial performance (CFP). Furthermore, it examines the factors that moderate the relationship between the two, including corporate reputation, customer satisfaction, ethical leadership, ownership concentration, institutional environment and market competition, based on legitimacy theory and stakeholder theory. The results show that the relationship between CSR and corporate performance is affected by corporate reputation, customer satisfaction, ethical leadership, ownership concentration, institutional environment and market competition. This paper may have implications for corporate management and policy makers.